Biomass for food or fuel : technology, food security and climate externality - Ho, Jie Jia (2014)
This study develops a utility model that maximizes social welfare. We solve this social planner problem to obtain the optimal allocation of biomass between food and fuel and evaluate the impact of technology. A minimum food mandate is then considered in relation to the controversial issue of food security. An extension that accounts for climate externality is built upon the existing model to internalize externality from greenhouse gas emissions for a more representative assessment.